The labor relations climate and management rights in urban school systems. The case of Philadelphia. With the assistance of L.R. Matlack, Ch.L. Wright [a.o.] (Industrial Research Unit, Wharton School, University of Pennsylvania, 1974)
With graphs, index and tabs.